1993
DOI: 10.1007/bf01712460
|View full text |Cite
|
Sign up to set email alerts
|

Panaritium ossale et articulare caused byMoraxella nonliquefaciens

Abstract: Only little is known about soft tissue, bone or joint infections caused by Moraxella spp. A case of panaritium ossale et articulare caused by Moraxella nonliquefaciens in an 80-year-old patient immunocompromised by diabetes mellitus and liver insufficiency is reported here. Surgery, local antiseptic treatment, and therapy with aminopenicillins plus beta-lactamase-inhibitors led to complete cure of the infection within 10 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann-Czylwik, 1993;Woodbury et al, 2009). While differences in colonization by S. aureus have been attributed to host factors such as host immunity, age, gender and/or environmental factors (García-Rodríguez & Fresnadillo Martínez, 2002), the data generated from these 100 anterior nares samples could not reveal any relationship between host factors and bacterial structure or colonization of a particular species.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann-Czylwik, 1993;Woodbury et al, 2009). While differences in colonization by S. aureus have been attributed to host factors such as host immunity, age, gender and/or environmental factors (García-Rodríguez & Fresnadillo Martínez, 2002), the data generated from these 100 anterior nares samples could not reveal any relationship between host factors and bacterial structure or colonization of a particular species.…”
Section: Discussionmentioning
confidence: 72%
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann‐Czylwik, ; Woodbury et al ., ).…”
Section: Discussionmentioning
confidence: 97%